Structure of Public Passenger Transport Lines in the Region of Prešov in Slovakia to Support the Development of an Integrated Transport System - Bulková, Zdenka; Škorupa, Milan; Kendra, Martin; Gašparík, Jozef; Zitrický, Vladislav (Applied sciences, 2024)
In the framework of sustainable development, the most important goal in the transport sector is sustainable mobility. It is necessary to improve the quality of the means of transport and the organisation of their operation in transport systems in addition to the management systems, coordination, and integration of individual types of transport. The aim of this paper is to propose a complex system of public transport lines in the region to achieve an effective transport service, in accordance with the principles of sustainable mobility, supporting the development of an integrated transport system. This research presents a proposal for the public transport lines of the region of Prešov in Slovakia, which is currently connected to an integrated transport system (IDS Východ). The proposal is defined by the tracing and functions of the lines, the mode of transport and headways on individual lines, the necessary number of vehicles for the operation of individual lines, transfer times at relevant points and directions, and the border of the radius of attractive daily commuting to the centre of the region, as well as a rough timetable for each line. Using an analytical hierarchical process (AHP method), we determine the two most suitable variants of traffic services. The results indicate that based on the multicriteria evaluation of these variants using descriptors, it is possible to determine the optimal variant of the transport service of the region, which will be introduced into a functional integrated transport system.